2013
DOI: 10.1002/zaac.201300091
|View full text |Cite|
|
Sign up to set email alerts
|

Electronic Origin of the Structural Anomalies of Zinc and Cadmium

Abstract: The electron distributions in position and in momentum space of the hcp metals magnesium and zinc are investigated experimentally and compared to results of quantum-chemical calculations. Furthermore, a survey is given on recent analyses of the bonding properties of zinc and cadmium, using the method of increments. The experimental deformation densities were obtained by refining multipole models to X-ray diffraction data sets measured at 100 K with either Mo-K α (Mg) or Ag-K α (Zn) radiation. The final R F val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…For Zn and Cd it has been found difficult to achieve simultaneously good agreement for structure, cohesive energy, and bulk modulus at the PBE, TS, and TS+SCS levels of theory, which can be achieved only by coupled-cluster calculations. 56 Here we want to examine the performance of the TS and TS/HI schemes for a class of intermetallic compounds known as Zintl phases, 57, 58 consisting of atoms with a large difference in electronegativity. The standard interpretation of the structure of Zintl phases is that due to the large electronegativity difference, electrons are transferred from the atoms with the lower electronegativity to those with higher electronegativity and that the anions form a sublattice with a structure similar to that of the isoelectronic neutral species.…”
Section: B Metals and Intermetallic Compoundsmentioning
confidence: 99%
“…For Zn and Cd it has been found difficult to achieve simultaneously good agreement for structure, cohesive energy, and bulk modulus at the PBE, TS, and TS+SCS levels of theory, which can be achieved only by coupled-cluster calculations. 56 Here we want to examine the performance of the TS and TS/HI schemes for a class of intermetallic compounds known as Zintl phases, 57, 58 consisting of atoms with a large difference in electronegativity. The standard interpretation of the structure of Zintl phases is that due to the large electronegativity difference, electrons are transferred from the atoms with the lower electronegativity to those with higher electronegativity and that the anions form a sublattice with a structure similar to that of the isoelectronic neutral species.…”
Section: B Metals and Intermetallic Compoundsmentioning
confidence: 99%
“…They reported that the thermal motion of Zn shows a striking anisotropy as expressed by a ratio / of ≈ 2.6 at 500 K [1]. The electronic origin of the structural anomalies of zinc was studied by Wedig et al using experimental and theoretical calculations [2]. Their findings indicated that the anomalies of c/a ratio are caused by 4s-3d electron interactions rather than anisotropy in thermal expansion, and they suggested that the anomalous hcp structure of zinc results from a kinetic balancing of the valence electrons, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings indicated that the anomalies of c/a ratio are caused by 4s-3d electron interactions rather than anisotropy in thermal expansion, and they suggested that the anomalous hcp structure of zinc results from a kinetic balancing of the valence electrons, i.e. through correlationmediated 4s-3d interactions [2].…”
Section: Introductionmentioning
confidence: 99%
“…1−5 Cd has more localized d electrons (in a closed 4d shell) than other transition metals in the same period, leading to intriguing chemical and physical properties, such as low melting points and structural anomalies. 6 Cd's diagonal relationship with Tl in the periodic table inspired us to look for new compounds based on its moderate electronegativity, as well as for the possibility that it might form compounds based on Cd clusters or polymeric frameworks analogous to (Tl) n n− in NaTl. 7 Many Zintl-like 8 compounds are known for binary alkali-metal−Cd solid-state systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among the late transition metals, cadmium (Cd) has been widely studied both experimentally and theoretically. Experimentally, it forms diverse, complex crystal structures ranging from NaCd 2 (Samson, 1962) and Cu 4 Cd 3 (Samson, 1967) to quasicrystals such as RE Cd ∼6 ( RE = rare earth). Cd has more localized d electrons (in a closed 4d shell) than other transition metals in the same period, leading to intriguing chemical and physical properties, such as low melting points and structural anomalies . Cd’s diagonal relationship with Tl in the periodic table inspired us to look for new compounds based on its moderate electronegativity, as well as for the possibility that it might form compounds based on Cd clusters or polymeric frameworks analogous to (Tl) n n – in NaTl .…”
Section: Introductionmentioning
confidence: 99%